ANALISIS KEMAMPUAN TENAGA PENDIDIK DALAM MENGGUNAKAN KOMPUTER UNTUK ADMINISTRASI KELAS TK NUR ILAHI PEKANBARU - Putri Clawson; Ratna Dewi (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2019)
This study aims to analyze how a teacher's ability to use computers for class administration is the ability to manage teaching and learning programs, the ability to manage classes in making classroom administration, the ability to manage teaching and learning interactions and the assessment of teacher performance results. This research is a qualitative study that takes the background of Nur Divine Divine Kindergarten Pekanbaru. Data collection is done by observation, interviews and documentation. The results of the research show that the ability of educators in using computers in Nur Divine Divine Kindergarten Pekanbaru implements several abilities in using computers for classroom administration. work was hampered so that it was not as scheduled, because two out of eight teachers had different difficulties in using computers to make the administration of their classes. The ability to use the computer can be said to be still lacking because the administration that is done is still not right at the time of completion, which should be given training for teachers to use computers, how dare teachers to use computers and support from other teachers is also lacking while the administration continues to run.